Feasibility study of a hiking project. Terraza Archaeological Site (Cafayate, Salta) - Ledesma, Rosana; Villarroel, Jimena; Cardozo, Rodrigo (Facultad de Filosofía y Humanidades. Museo de Antropología, 2023)
After the confinement due to the Covid 19 pandemic, the Terraza family presented a family tourism entrepreneurship project to be developed in the municipality of Cafayate, province of Salta. In response to the requirements of the provincial Ministry of Tourism, the entrepreneurs asked CONICET that the archaeological team investigating the area carries out a Technichal Advisory Service of a touristic project of cultural management. The report included a feasibility study of the trails proposed by tourism managers, the study of the carrying capacity of the archaeological site for hiking, a diagnosis and current state of the archaeological complex, an evaluation of the authenticity of the goods and the study of the site. A series of recommendations were also made, with a care guide for touring the site and projections of future work on site aimed at developing a management plan. The hiking project is feasible if the recommendations are followed and, in the suggested sections, being necessary to carry out monitoring and adjustments of the load capacity once the visits begin.